Alternative Total Lagrangian Formulations for Corrected Smooth Particle Hydrodynamics (CSPH) Methods in Large Strain Dynamic Problems - Bonet, Javier; Kulasegaram, Sivakumar (European Journal of Computational Mechanics, 2002)
This paper discusses alternative Lagrangian formulations for smooth particle hydrodynamics method. These Lagrangian formulations are here employed in solving large strain problems that involve e/asto-plastic and hyperelastic materials. It has previously been shown in the literature that the Lagrangian formulation for continuum eliminates the problem of tension instability which is generally coupled with Eulerian continuum formulation of smooth particle hydrodynamics and other meshless methods. This paper presents the details of the methodologies used in formulating Lagrangian smooth particle hydrodynamics method and their characteristics.